The Jurisprudence of Disagreement and the Rejection of Fanaticism as a Pillar of Human Rights and its Role in Accommodating Pluralism and Religious Moderation: فقه الخلاف ونبذ التعصب كركيزة من ركائز حقوق الإنسان ودوره في استيعاب التعددية والاعتدال الديني (دراسة وصفية تحليلية لحقوق الإنسان الإسلامية وفقه الخلاف والتعددية وتأثيرهما في استعاب الآخر) - Yusuf Hanafi; Salih Abdulrahman Alsounusi Yousuf (PT. Pusmedia Group Indonesia, 2023)
Religious moderation, understanding and assimilating others, and dealing with them despite intellectual and methodological differences is required and commendable, but it only comes from understanding the other and respecting his right to thought and belief, and from here we must stand on the jurisprudence of disagreement and know the human rights granted by Islam to creation of different sects and differences, and in this article dealt with some definitions of important terms, and mentioned the Islamic texts that talked about the subject of study, and talk about human rights in Islam, and exposure to disagreement and difference, The causes and methods of treatment are mentioned in the results, and I followed the descriptive analytical approach in this article